2012
DOI: 10.3109/00016357.2012.700066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of osteoblast cell culture on the bone implant contact

Abstract: Implant-bone connection was better in the OCC-PRP group compared with the PRP group and the empty defect group. The use of OCC-PRP combination was effective on healing. The BIC value was increased significantly by OCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Full texts of the remaining 14 publications were obtained for review and possible inclusion in the systematic review and meta‐analysis. Out of these, four articles were further excluded ( κ = 1.00) (Hao et al ; Hoşgör et al ; Zhang et al ; Ribeiro et al ) for reasons indicated in Table . Manual search of reference lists of selected studies yielded no additional articles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Full texts of the remaining 14 publications were obtained for review and possible inclusion in the systematic review and meta‐analysis. Out of these, four articles were further excluded ( κ = 1.00) (Hao et al ; Hoşgör et al ; Zhang et al ; Ribeiro et al ) for reasons indicated in Table . Manual search of reference lists of selected studies yielded no additional articles (Fig.…”
Section: Resultsmentioning
confidence: 99%